Chemoenzymatic epoxidation of alkenes with Candida antarctica lipase B and hydrogen peroxide in deep eutectic solvents. Issue 21 (21st February 2017) - Zhou, Pengfei; Wang, Xuping; Yang, Bo; Hollmann, Frank; Wang, Yonghua
Abstract : Epoxides are important synthetic intermediates for the synthesis of a broad range of industrial products. Abstract : Epoxides are important synthetic intermediates for the synthesis of a broad range of industrial products. This study presents a promising solution to the current limitation of enzyme instability. By using simple deep eutectic solvents such as choline chloride/sorbitol, significant stabilization of the biocatalyst has been achieved leading to more robust reactions while using environmentally more acceptable solvents as compared to ionic liquids.